City Planning Evolution - Urban Development Directions in the Transition Period - Mircea Grigorovschi (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2010)
Urban evolution post 1989 has a series of specific characteristics mainly on a spatial-territorial plane. Determination of the main developing factors and urban evolution directions (dimensions, rhythm, expansion level, centrifugal and axial character, concentric, centripetal, functional evolution, tendencies and social implications, etc.) represents a necessity and obligation for action from professionals in urban and landscaping fields. This necessity even arises from the perspective of the need for realizing strategies, planning, documentation and urban studies, which must intervene correctively in the evolution of areas with structural problems and to guide urban evolution towards the main goal namely the growth in residential quality of life in human settlements.